Z세대 대학생의 긍정적인 자아정체감 형성을 위한 모바일앱 서비스 제안 - 이하랑(Ha-Rang Lee); 전우정(Woo-Jeong Chon) (디지털콘텐츠학회논문지, 2022)
본 연구는 Z세대의 대학생의 긍정적인 자아정체감 형성을 돕는 모바일 앱 서비스를 목적으로 문헌 조사와 서비스 디자인 도구를 활용한 사용자 조사를 통하여 사용자의 관점으로 서비스를 제안하였다. 사용자 조사를 통해 Z세대 대상자들이 자아정체감 탐색 과정을 긍정적으로 받아들이며 대상자 마다 다양한 방법으로 자신을 탐색하기 원한다는 점, 관계를 통해 자아정체감에 영향을 받고 싶어 하는 점 등을 발견하였다. 이를 반영하여 모바일 앱 서비스의 컨셉인 ‘다채로운(Colorful)’, ‘커스터마이징 (Customizing)’, ‘연대 (Solidarity)’, ‘선순환(Virtuous Cycle)’을 설정하였으며 서비스 영역을 ‘자기탐색’과 ‘커뮤니티’로 나누어 서비스의 흐름을 서비스 블루프린트로 제작하였다. 이후 모바일 앱 서비스의 핵심 기능을 도출하고, 정보구조도(I.A.) 설계 후 주요 기능에 대한 최종 디자인을 제안하였다. 본 연구는 ‘디지털 네이티브’인 Z세대의 특성을 고려하여 그들의 자아정체감 형성을 위한 모바일 앱 서비스를 기획하였으며, 이는 서비스 디자인 방법론을 활용하여 사용자의 경험을 바탕으로 핵심기능을 도출하여 서비스를 제안하였다는 점에서 그 의의가 있다. This study proposed service from the perspective of a user through literature review and user research using a service design tool for mobile app service that helps form self-identity university students in Generation Z. Through user research, it was found that Generation Z subjects positively accept the self-identity search and want to explore in various ways and that they want to be influenced by self-identity through relationships. Reflecting this, the concepts such as 'Colorful', 'Customizing', 'Solidarity', and 'Virtuous Cycle' were set, and the service area was divided into 'self-exploration' and 'community' and the flow of service Blueprinted. After that, the core functions of the mobile app service were derived, and the final design for the main functions was proposed after the design of the Information Architecture (I.A.). This study planned a mobile app service to form their sense of self-identity in consideration of the characteristics of Generation Z, which is 'digital native', and this is meaningful in that it derived core functions based on user experience and proposed services. KCI Citation Count: 0